2015
DOI: 10.1080/00222933.2014.979260
|View full text |Cite
|
Sign up to set email alerts
|

Anisakis simplexcomplex (Nematoda: Anisakidae) in zooplankton communities from temperate NE Atlantic waters

Abstract: The euphausiid Nyctiphanes couchii and an unidentified mysid have been found, for the first time, with third-stage larvae (L 3 ) of the Anisakis simplex complex in the mesozooplanktonic community of the coastal upwelling system in Galicia (NW Spain). Parasite larvae were molecularly identified using the internal transcribed spacer (ITS) region. The prevalence of these parasites in the euphausiid population was 0.0019%. The existence of parasites in a variety of mesozooplankton organisms suggests that the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 46 publications
(54 reference statements)
1
24
0
Order By: Relevance
“…Results revealed that all the fish species were parasitized by Anisakis type I larvae with a global prevalence of 33.65%. Anisakis species have been reported in a wide range of marine pelagic fish and cephalopods [16][17][18], most of them encompassing an important part of the human diet. As fish is considered a staple of the healthy diet, particularly in Spain [19], the results reported herein pinpoint the fish species with a high risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Results revealed that all the fish species were parasitized by Anisakis type I larvae with a global prevalence of 33.65%. Anisakis species have been reported in a wide range of marine pelagic fish and cephalopods [16][17][18], most of them encompassing an important part of the human diet. As fish is considered a staple of the healthy diet, particularly in Spain [19], the results reported herein pinpoint the fish species with a high risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…and of the A. simplex complex (A. simplex s.s. and A. pegreffii) in NW Iberian Peninsula waters (Gregori et al 2012(Gregori et al , 2015. It was additionally reported as intermediate host of A. simplex on the Scottish East Coast and of Hysterothylacium sp.…”
Section: Feeding and Transmission Pathwaysmentioning
confidence: 94%
“…Smith (1983) proposed that euphausiids were the major intermediate host of A. simplex s.l., in the northeast Atlantic and northern North Sea, and perhaps universally. Recently, Gregori et al (2015) detected the occurrence of larvae of A. simplex (s.s.) and A. pegreffii in the euphausiid Nyctiphanes couchii, justifying the co-occurrence of both species in the same fish species, and its sympatry in the northeast Atlantic. However, other invertebrate species were also indicated as host candidates for Anisakis species, such as copepods (eg.…”
Section: Discussionmentioning
confidence: 99%